Stillbirths - Determining the associated factors and causes according to relevant condition at death: an experience from Pokhara, Nepal - Shrestha, Junu; Shrestha, Rami; Gurung, Sonam (Journal of Nobel Medical College, 2018)
Background: Stillbirth contributes significantly to perinatal mortality. This study was conducted with aim to determine various factors associated with it and to define the causes of stillbirth according to relevant condition at birth.Materials and Methods :This is prospective cross-sectional study conducted in the Department of Obstetrics and Gynaecology of Manipal Teaching Hospital from July 2015 to June 2017. All cases of stillbirth occurring during antenatal or intrapartum period after 28 weeks of gestation or fetus weighing 1000 grams or more were included. Detailed demographic parameters were noted. After delivery, fetus, placenta, umbilical cord and amniotic fluid were noted in detail. Data was entered in SPSS version 16 and analysis done.Results: The stillbirth rate was 22 per 1000 births. Low educational level of women, lack of antenatal care, multiparous status, gestational age less than 34 weeks, low birth weight and male gender of fetus were found to be significantly associated with stillbirths. The cause of fetal death could be identified according to relevant condition at death in 84% of cases. Only in 16%, the cause of stillbirth was not identified. Intrauterine growth restriction was the commonest cause of stillbirth (22%), followed by congenital anomalies (15%) and hypertensive disorders of pregnancy (14%). Other causes were abruptio (7%), intrapartum asphyxia (7%) and rupture uterus (5%). Other minor causes were anemia, diabetes, cord prolapse and amniotic fluid abnormalities.Conclusion :Low level of education, lack of quality antenatal care, multiparity, low gestational age and birth weight and male sex of fetus were factors associated with stillbirth. The cause of stillbirth was identified in most of the cases and largely was due to intrauterine growth restriction.Journal of Nobel Medical CollegeVolume 6, Number 2, Issue 11, July-December 2017, 58-65